Routledge handbook of environmental policy - Andersen, Mikael Skou (earthscan from Routledge, 2023)
"This Handbook provides a state-of-the-art review of research on environmental policy and governance. The Routledge Handbook of Environmental Policy has a strong focus on new problem structures – a perspective that emphasizes the preconditions and processes of environmental policymaking – and a comparative approach that covers all levels of local, national, and global policymaking. The volume examines the different conditions under which environmental policymaking takes place in different regions of the world and tracks the theoretical, conceptual, and empirical developments that have been made in recent years. It also highlights emerging areas where new and/or additional research and reflection are warranted. Divided into four key parts, the accessible structure and the nature of the contributions allow the reader to quickly find a concise expert review on topics that are most likely to arise in the course of conducting research or developing policy, and to obtain a broad, reliable survey of what is presently known about the subject. The resulting compendium is an essential resource for students, scholars, and policymakers working in this vital field."
Keywords: Umweltpolitik; Aufsatzsammlung